2018
DOI: 10.1016/j.whi.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Drug Use, Violence, and Depressive Symptoms with Sexual Risk Behaviors Among Women with Alcohol Misuse

Abstract: A higher prevalence of sexual risk behaviors by women with alcohol misuse combined with drug use, IPV, and depressive symptoms supports the need for alcohol interventions addressing these additional comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Existing literature has documented a relationship between poverty and mental illness such as depression [ 10 , 36 , 37 ]. For instance, a study by Lee et al revealed that depression increased women's lifetime exchange of sex for drugs or money, increasing the prevalence of sexual risk behaviors [ 38 ]. Similar findings were reported by Musisi and colleagues in their study about primary partnerships in Uganda, where depressive symptoms were associated with higher desires to engage in unprotected sex for financial gains [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has documented a relationship between poverty and mental illness such as depression [ 10 , 36 , 37 ]. For instance, a study by Lee et al revealed that depression increased women's lifetime exchange of sex for drugs or money, increasing the prevalence of sexual risk behaviors [ 38 ]. Similar findings were reported by Musisi and colleagues in their study about primary partnerships in Uganda, where depressive symptoms were associated with higher desires to engage in unprotected sex for financial gains [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, additive interactions between syndemic conditions on CAI were assessed and stratified by race and ethnicity. The relative excess prevalence owing to interaction (REPI) and 95% CIs were estimated for selected pairs of syndemic conditions (22)(23)(24)(25)(26)(27). Pairs of syndemic conditions were selected based on empirical evidence of potential interactions on CAI among transgender women (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Substance use has been shown to be a risk factor for both risky sexual behaviours (such as sex while intoxicated, or condomless sex with a casual partner, transactional sex, etc.) and being exposed to non-consensual sex or intimate partner violence [69][70][71][72][73][74][75][76], placing them at a higher risk of unintended pregnancy.…”
Section: Plos Onementioning
confidence: 99%